DIGITALIZATION TOWARDS READING HABITS: HOW DO TODAY’S EFL UNIVERSITY STUDENTS READ? - Benni Abdullah; Kurniasih -; Nuse Aliyah Rahmati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: The simple availability and accessibility of online reading materials is perceived a benefit for reading culture, and at the same time, Internet services can be seen as a challenge to typical print reading. This study was designed to examine thepattern of todays’ EFL university students on reading habits in the digital age and to examine the significant of internet on EFL reading habits. In order to have a broad overview of the current reading habits, a questionnaire was conducted among 36 fourth-year students of Universitas Islam Malang. Creswell’s (2009) method was used to analyze the data. The findings showed that respondent enjoy online reading because internet and electronic devices create a perfect. Internet affects the respondent’s reading, nowadays, many respondents are surfing the internet, doing more scrolling or non-linear reading, and attempted to get the information they’re needed. Beside, the students are still interesring in reading printed books.Keywords: Digitalization, Reading Habits, University Students